2023
DOI: 10.1097/aog.0000000000005121
|View full text |Cite
|
Sign up to set email alerts
|

Nonoperative Management of Pelvic Organ Prolapse

Abstract: Pelvic organ prolapse (POP) is defined as the descent of one or more of the anterior, posterior, or apical vagina. It is a common condition, with up to 50% of women having prolapse on examination in their lifetimes. This article provides an overview of the evaluation and discussion of nonoperative management of POP for the obstetrician-gynecologist (ob-gyn), with consideration of recommendations from the American College of Obstetricians and Gynecologists, the American Urogynecologic Society, and the Internati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 70 publications
0
1
0
Order By: Relevance
“…A systematic review, including 89 articles, reported that more than 50% of women continued pessary use and had an obvious improvement in their quality of life, sexual function, and body perception [74]. Complications from pessaries insertion include discontinuation, local infection, vaginal bleeding, the risk of developing vaginal erosions or discharge, and new bowel and bladder symptoms [75,76]. Although these are typically minor, an appropriate short-term removal or vaginal estrogen therapy should be considered.…”
Section: Pessary Usagementioning
confidence: 99%
“…A systematic review, including 89 articles, reported that more than 50% of women continued pessary use and had an obvious improvement in their quality of life, sexual function, and body perception [74]. Complications from pessaries insertion include discontinuation, local infection, vaginal bleeding, the risk of developing vaginal erosions or discharge, and new bowel and bladder symptoms [75,76]. Although these are typically minor, an appropriate short-term removal or vaginal estrogen therapy should be considered.…”
Section: Pessary Usagementioning
confidence: 99%